Developing Muslim-Friendly Tourism in Pasuruan City, East Java: A SWOT Analysis Approach Aligned with Sustainable Development Goals - Gunawan, Rachmat Bryando; Risfandini, Andini; Supriadi, Bambang; Rana, Shreema (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study examines the potential and challenges of developing Muslim-friendly tourism in Pasuruan City, East Java, through a SWOT analysis framework integrated with the Sustainable Development Goals (SDGs). Using qualitative methods involving field observation, document analysis, and stakeholder interviews, the research identifies key internal and external factors influencing tourism development. The findings reveal that Pasuruan City has strong potential, driven by its Islamic cultural heritage, strategic location, and active community participation. However, the city faces notable weaknesses in infrastructure, human resource competencies, and stakeholder coordination. Opportunities arise from the global growth of the halal tourism market and government support for sustainable tourism initiatives, while threats include competition from nearby destinations, policy inconsistency, and safety concerns. The study emphasizes the importance of aligning tourism development strategies with SDGs 8 (Decent Work and Economic Growth), 9 (Industry, Innovation, and Infrastructure), 11 (Sustainable Cities and Communities), and 17 (Partnerships for the Goals). Strengthening digital promotion, enhancing service quality, and fostering cross-sector collaboration are recommended to improve competitiveness and ensure inclusive, sustainable growth. The findings contribute to a deeper understanding of how medium-sized cities in Indonesia can strategically position themselves within